Adaptive planning of 3G/4G systems using Q-analysis or polyhedral dynamics (2004)
In this paper we present a method for use Q-analysis in the initial planning process and later dynamic adaptation for 3G/4G cellular systems that intends to balance load in order to maximize capacity and reduce lost and dropped calls independently of the type of service. We support our proposal on dynamic simulations made with an own developed tool for dynamic simulations of CDMA systems, and show initial results that partially probe our proposed method.